Edible insects: a food security solution or a food safety concern?. (1st April 2015) - Belluco, Simone; Losasso, Carmen; Maggioletti, Michela; Alonzi, Cristiana; Ricci, Antonia; Paoletti, Maurizio G.
Abstract: Insect species intended for human consumption should be selected, managed, and prepared by taking into account traditional knowledge acquired in countries where insect consumption is customary. Existing evidence indicates that edible insects reared under controlled conditions are expected to pose no additional hazards compared with traditional animal products. Food safety research and regulatory issues should be implemented by addressing the insect food chain, taking into account species features, insect origins, farm management, and environmental conditions.